Research on guest comfort and satisfaction with indoor environmental quality in former GBI-certified green hotels: a study case from Malaysia - Abdulaali, Hayder Saadoon; Usman, Ismar M. S.; Alawi, Mohsen; Alqawzai, Shagea (Frontiers in Built Environment, 2025)
This study examines the impact of Indoor Environmental Quality (IEQ) on guest comfort and satisfaction in former Green Building Index (GBI)-certified green hotels in Malaysia’s historic cities, including Kuala Lumpur, Melaka, and Penang. With many hotels moving away from certification, it highlights the need to maintain high environmental and comfort standards. The research evaluates IEQ performance, suggests additional parameters, and explores how comfort mediates the relationship between IEQ and satisfaction. Eight hypotheses were tested, focusing on indoor air quality (IAQ), thermal comfort, lighting, acoustics, visual comfort, building features, decoration, and indoor greenery. A survey of 700 hotel guests resulted in 384 valid responses, confirming that IEQ significantly influences comfort and satisfaction. Among the factors, acoustic/noise (Beta = 0.305), IAQ (Beta = 0.221), and building characteristics (Beta = 0.167) were the most impactful, followed by thermal comfort, lighting, decoration, visual comfort, and indoor greenery. Regression analysis showed a strong link between guest comfort and satisfaction, with comfort as a key mediator. Challenges included noise, thermal discomfort, and lighting problems. The study emphasizes the importance of air quality, thermal comfort, and noise management while balancing aesthetic elements like greenery and decoration to improve guest experiences. It offers valuable insights for hotel operators, advancing sustainable practices and guest satisfaction in green-certified hotels.